The Family Satisfaction Towards to Nursing Services - Dhiaz Feby Elsantriya; Riama Marlyn Sihombing; Elissa Oktoviani Hutasoit (UIMA Press, 2022)
Background: Nursing service quality can provide satisfaction to the patients and their families. Satisfaction occurs after analysing perceptions of service performance manifested in feelings of pleasure or disappointment. Based upon a survey during September 2019, one private hospital in central Indonesia found 30% of the family members were dissatisfied with nursing services. Respondents evaluated nurses were late replying to bells, and the explanation of nursing intervention was not recognized by family members. Objectives: The study aimed to analyse the factors related to family satisfaction toward nursing services. Methods: A quantitative inferential with a cross-sectional approach. A purposive sampling was selected among 214 respondents. Data collection using a questionnaire that has been examined on validity and reliability which processed quantitatively and analysed with Fishers exact and logistic regression tests. Results: More than half of the respondents were female and less than half were aged 26-35 years. Half had higher education. There was a significant correlation between tangible (p=0.001), reliability (p=0.001), responsiveness (p=0.001), empathy (p=0.001) and assurance (p=0.001) with family satisfaction. Reliability remains the most dominant factor that affected family satisfaction. Good reliability has a 0.048 times greater chance of increasing family satisfaction compared to poor reliability. Conclusion: The family members were not satisfy with the nursing services. Management to improve nursing services might assess the families desire for the reliability of nursing services so expect satisfaction will increase.